Metabolism and immune status during transition period influences the lactation performance in Zebu (Bos indicus) cows - WANKHADE, PRATIK RAMESH; MANIMARAN, AYYASAMY; KUMARESAN, ARUMUGAM; JEYAKUMAR, SAKTHIVEL; RAMESHA, KEREKOPPA P; SEJIAN, VEERASAMY; RAJENDRAN, DURAISAMY; BAGATH, MADIAJAGAN; SIVARAM, MUNIANDY (The Indian Journal of Animal Sciences, 2018)
We evaluated the changes in the concentration of innate immune molecules (haptoglobin: Hp, serum amyloid A: SAA, IL-6, TNF-α, IL-1β, and IL-8), energy indicators [NEFA, dry matter intake (DMI) and body condition scoring (BCS)] during the transition period in dual-purpose Zebu (Deoni breed) cows in relation to milk yield. Blood collection was done at weekly intervals (–21±2, –14±1, –7±1, d pre-partum, day 0 (date of calving) and 3±1, 7±1, 14±1, 21±2 d postpartum period) for estimation of above plasma variables using commercially available bovine specific ELISA kits. We also recorded DMI and BCS during the corresponding period. Transition cows were classified based on their milk yield during the study period as high (6), medium (6) and low (6) yielding cows and data were analyzed by using Mixed-model repeated measure analysis. High yielding (HY) cows had significantly higher concentrations of SAA, TNF-α, and IL-6 during pre-partum and early postpartum period than low yielding (LY) cows. DMI was significantly higher in HY cows than MY (3rd and 7th d) or LY cows (21st d) while, BCS was significantly higher in HY than LY cows during pre-partum period (-7th d). LY cows had significantly higher concentration of NEFA during the postpartum period (14th and 21st d). It is concluded that the active functioning of the immune system and more dry matter intake in transition Deoni cows enabled to synthesise more milk during the postpartum period.